2014
DOI: 10.2147/jmdh.s70470
|View full text |Cite
|
Sign up to set email alerts
|

Web-based collaboration in individual care planning challenges the user and the provider roles – toward a power transition in caring relationships

Abstract: Background and objectiveThe Individual Care Plan (ICP) was introduced in Norway to meet new statutory requirements for user participation in health care planning, incorporating multidisciplinary and cross-sector collaboration. A web-based solution (electronic ICP [e-ICP]) was used to support the planning and documentation. The aim of this study was to investigate how web-based collaboration challenged user and professional roles.MethodsData were obtained from 15 semistructured interviews with users and eight w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 35 publications
0
19
0
1
Order By: Relevance
“…Limited time for care planning and a lack of awareness of the value of PDCP are barriers across diverse care settings (Bjerkan, Vatne, & Hollingen, 2014). Furthermore, in LTC, many—perhaps most—staff are not trained in communication approaches that might engage residents in care planning (Børøsund, Ruland, Moore, & Ekstedt, 2014; Savundranayagam, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited time for care planning and a lack of awareness of the value of PDCP are barriers across diverse care settings (Bjerkan, Vatne, & Hollingen, 2014). Furthermore, in LTC, many—perhaps most—staff are not trained in communication approaches that might engage residents in care planning (Børøsund, Ruland, Moore, & Ekstedt, 2014; Savundranayagam, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Adoption of health information technology that supports individuals’ engagement in care planning, or communication across individuals and care providers, also facilitates PDCP (Baumann, LupPlace, & Quasey, 2010; Bjerkan et al, 2014). Using simple tools, Lankarani‐Fard et al (2010) found that a card‐sorting game can be effective in identifying individuals’ values and priorities for end‐of‐life care.…”
Section: Resultsmentioning
confidence: 99%
“…In the various self-management interventions also the relationship among patients and healthcare professionals is challenged. Bjerkan et al [6] examined the impact of an ICT based collaboration tool in individual care planning and realized that in some cases, a power transition took place in the care process, which led to patient empowerment. On the other hand, the study of Urowitz et al [5] about the impact of a diabetes self-management portal in patients revealed a grey area in the roles that the physicians should play in the facilitation of disease management.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of theories and tools emerging in technical and social sciences [1720] and positive computing [21] may aid in examining recovery-relevant issues such as self-esteem, stigma, power, self-disclosure, self-regulation, writing therapy and help-seeking behavior [1315] and how connecting with others through Internet may enable users to shape the nature of the services in line with recovery principles [17]. However, the opportunities provided by these theories and tools need to be incorporated into studies that specifically address how they may advance recovery processes.…”
Section: Discussionmentioning
confidence: 99%
“…Literature suggests that Internet can facilitate empowerment processes on a personal, interpersonal, group and citizen level [13] exemplified by increased access to social support and reduced stigma [14], power transitions between providers and service users [15] and person-centered services by allowing flexible and individually tailored services in homes and daily lives [16, 17]. At the same time, Internet-related technologies such as self-help apps, social media and virtual reality are developing so rapidly that there is a need to proactively identify and assess ways to exploit their benefits and limit their pitfalls.…”
Section: Introductionmentioning
confidence: 99%